Immigration in La Araucanía, How do Haitians, Colombians and Venezuelans Live This Process? - Baeza-Rivera, María José; Salinas-Oñate, Natalia; Salazar-Fernández, Camila; Larenas Said, Josefa; Araneda Leal, Leslie (Revista de Psicología, 2022)
The migration process and adaptation to the host culture present a series of unique challenges for immigrants, which affect their level of psychosocial adjustment. This study seeks to characterise three groups of immigrants. Using an intentional snowball-type sampling, 150 immigrants were surveyed, from Colombia (n = 50), Venezuela (n = 50), and Haiti (n = 50). All were over 18 years and resided in the region of La Araucanía. The participants answered scales of acculturative stress, perceived discrimination, emotions associated with discrimination, acculturation strategies, social support, dispositional optimism, and sociodemographic questions. The data were analysed through descriptive and comparative analyses between groups. Results revealed that the three groups used the integration strategy to a greater extent. However, the acculturation process presented differences according to the country of origin. Thus, Haitian immigrants reported the most unfavourable indicators, while Venezuelans presented the most favourable. These results allow us to understand the migratory process in context, considering particular characteristics of each group, and the conditions of the host culture. Each group presents a differentiated profile that informs how the cultural interactions typical of migration are experienced.